Assessing Corporate Social Responsibility From the Perspective of the Local Community - Romadhona, Mochamad Kevin; Oktafenanda, Rachmat Dimas; Kinasih, Sri Endah (UI Scholars Hub, 2024)
Looking through the eyes of the local community is crucial for a successful corporate social responsibility (CSR) program. Within a local context, it is essential to understand the community’s perception and find the possible gaps within such a CSR program. Such assessment can be a way to identify aspects that are considered essential and beneficial by the community. This article presents the assessment of the CSR program of a particular company and its impact perceived by the local community. This study used quantitative research methods and elaborated with qualitative methods to gain a comprehensive overview of the community’s perception of an existing CSR Program conducted by the AIO Company in Pasuruan, East Java, Indonesia. The data was collected through a structured questionnaire to obtain information from 100 respondents in Pacar Keling Village, followed by in-depth interviews. Based on the data, it is found that the community perceived various programs offered by the company with positive and negative insights due to the lack of community involvement during the program planning. Some programs, like food and health-related are well-received. However, some are perceived as unsuitable for the community, suggesting inaccuracies in determining the target recipients of such programs and, thus, limited engagement from the targeted community. Assessing the impact of such a CSR program shows the importance of engaging the local community as a significant stakeholder, fully extending the positive public perceptions, and maintaining the company’s goodwill and ethics.